Partisipasi Masyarakat dalam Proses Perencanaan Pembangunan Desa (Studi di Desa Cialam Jaya Kecamatan Konda Kabupaten Konawe Selatan) - Manguntara, La (Jurnal Pendidikan Siber Nusantara, 2023)
This study aims to determine and describe community participation in the village development planning process in Cialam Jaya Village, Konda Subdistrick, South Konawe Districk. The method used is this study is qualitative descriptive. The location of the research was in Cialam Jaya Village, Konda Subdistrick, South Konawe Districk. The types and sources of data used in this study are primary and secondary data. In the proses of the data collection techniques used methods are obsrvasion methods, interviews and documentation, so as to be able to describe various matters relating to community participation in the village development planning process in Cialam Jaya Village. The data obtained were analyzed qualitatively and described in descriptive form. The results showed that community participation in the village development planning process in the village of Cialam Jaya in terms of involvement in meetings or deliberations, providing data and information, preparation of development plan designs, determining priority scales and making decisions is still not good, this is due to lack of community understanding of the importance community involvement in the village development planning process.